Integration of China's Capital Markets on Global Capital Markets Before and During the First Case of Covid 19 (SSEC, NYSE, JCI, AXJO). - Maikel Sanger; Ivonne S. Saerang; Willem J. F. A. Tumbuan (Research Parks Publishers, 2021)
The world is currently being shaken by a great pandemic, namely Covid 19 (Corona Virus Disease). The increase from day to day in the number of patients infected with the COVID-19 virus is difficult to control and a clear and straightforward plan is needed from the government to tackle this problem. The first case of covid 19 appeared in Wuhan, China at the end of 2019. This study aims to see the degree of closeness of the relationship between the Chinese, American, Indonesian and Australian capital markets before and during the First Case of Covid 19. The analytical technique used is correlation with the Pearson approach. product moments. Where the population used is 90 days before the case and 90 days when the first case of covid 19 occurs.